Rifampicin resistance and associated factors of Mycobacterium tuberculosis among pulmonary tuberculosis-suspected patients in the Amhara National Regional State Comprehensive Specialized Hospitals, Ethiopia - Tebelay Dilnessa; Feleke Moges; Belay Tessema; Workagegnehu Hailu; Baye Gelaw (PLoS ONE, 2026)
Background Tuberculosis (TB) remains a major public health challenge globally, with drug-resistant strains, particularly rifampicin-resistant Mycobacterium tuberculosis (RR-MTB), which poses serious challenges for treatment and control. Rifampicin resistance is widely recognized as a key surrogate marker for multidrug-resistant MTB and is associated with poor treatment outcomes and increased transmission risk. Ethiopia is among the high-TB-burden countries, and the Amhara National Regional State continues to report significant tuberculosis morbidity and mortality. Objective To assess the prevalence, rifampicin resistance patterns, and associated factors of M. tuberculosis among pulmonary tuberculosis-suspected patients at the Amhara National Regional State Comprehensive Specialized Hospitals, Northwest Ethiopia. Methods A multicenter prospective cross-sectional study was conducted among pulmonary tuberculosis-suspected patients attending the Comprehensive Specialized Hospitals from April 2023, to May 2025. Socio-demographic and associated factors data were collected using semi-structured questionnaires. Sputum was collected and tested using GeneXpert MTB/RIF assay to detect M. tuberculosis and rifampicin resistance. Data were entered into SPSS version 28 for analysis. Binary logistic regression was applied to assess the relationship between predictors and the prevalence of M. tuberculosis, and rifampicin resistance. Variables with a p -value < 0.05 at 95% confidence interval in multivariable logistic regression were considered statistically significant. Results Among 2548 pulmonary tuberculosis (PTB)-suspected participants, the overall prevalence of M. tuberculosis (MTB) was 150/2548 (5.9%). Rifampicin resistance was detected in 19/150 (12.7%) of MTB-positive cases, urban residents 7/70 (18.6%), and low education (grades 1−4), 3/15 (20.0%). In multivariable logistic regression analysis, rural residence was associated with reduced PTB infection compared with urban residence (AOR: 0.23; 95% CI: 0.06–0.79; p = 0.020). Previous antibiotic use (AOR: 9.17; 95% CI: 2.01–28.14; p = 0.001), HIV-positivity (AOR: 3.73; 95% CI: 2.40–7.78; p = 0.001) and alcohol consumption (AOR: 7.10; 95% CI: 4.99–20.86; p = 0.001) were independently associated with increased MTB infection. Rural residents showed significantly lower odds of rifampicin-resistant MTB compared to urban counterparts (AOR: 0.35, 95% CI: 0.12–0.99, p = 0.048). Conclusion The prevalence of M. tuberculosis infection and rifampicin resistance remains significant in the study area. The strong association between prior antibiotic use, HIV-positivity and alcohol consumption with M. tuberculosis highlights the need for targeted case-finding, improved diagnosis, rational antibiotic use, and focused health education interventions.